Reversal of Vitamin K Antagonist Therapy Before Thrombolysis for Acute Ischemic Stroke. Issue 10 (October 2018) - Chausson, Nicolas; Soumah, Djibril; Aghasaryan, Manvel; Altarcha, Tony; Alecu, Cosmin; Smadja, Didier
Abstract : Background and Purpose—: Acute ischemic strokes under vitamin K antagonist (VKA) treatment are not uncommon, but intravenous thrombolysis (IVT) is not recommended for international normalized ratio (INR) >1.7 because of the excess bleeding risk. However, VKA-induced anticoagulation can be easily reversed by IV infusions of 4-factor prothrombin complex concentrate bolus and vitamin K. Our pilot study aimed to determine whether IVT immediately after anticoagulation reversal could be feasible and safe in acute ischemic stroke patients under VKA with INR >1.7. Methods—: Consecutive acute ischemic stroke patients, otherwise eligible for IVT except for VKA intake and INR >1.7, were given IVT after infusing 4-factor prothrombin complex concentrate and vitamin K. Safety and efficacy were assessed clinically and by cerebral imaging at 24 hours. Results—: Twenty-six patients (age, 77.8±12.8 years; atrial fibrillation, 84.6%; initial National Institutes of Health Stroke Scale, 11.6±5.6) were prospectively included. INR values were 2.3±0.6 initially and 1.3±0.2, 5 minutes postreversal. No symptomatic intracranial hemorrhage or thrombotic events occurred during the first 3 days. One patient developed major systemic hemorrhoidal bleeding that required blood transfusion; 61.5% of the patients were independent (modified Rankin Scale score of ⩽2) at 3 months. Conclusions—: A reversal strategy of 4-factor prothrombin complex concentrate bolus and vitamin K before IVT could be feasible and safe in acute ischemic stroke patients under VKA with INR >1.7. Well-designed, randomized controlled trials are warranted to confirm these preliminary findings. Abstract : Supplemental Digital Content is available in the text.